Investment Attractiveness of the Russian Energy Sector MNCs: Assessment and Challenges - Gorodetskaya, Olga Yu.; Alekseeva, Gulnara I.; Artamonova, Kira A.; Sadovnikova, Natalia A.; Babich, Svetlana G.; Iamalova, Elvira N.; Tarasov, Anatoliy M. (International Journal of Energy Economics and Policy, 2021)
Being the most important economic sectors, the energy sector provides significant profits for the Russian economy and is largely dependent on the functioning of several multinational corporations such as Rosneft, Gazprom and Lukoil. Investments in these companies have always been important drivers for the Russian economy. New conditions of the global economy create serious challenges for the sector; therefore, the investment attractiveness of the sector is changing. The authors propose a new approach to the analysis of investment attractiveness, based on the conjugation of technical financial analysis, reflecting the internal factors that affect the companies’ performance, and the SWOT analysis of the industry combined with the Doing Business Rankings that give a full picture of the external factors of investment attractiveness. This methodology makes it possible to identify the main specific characteristics of Russian MNCs and develop an investment strategy in the Russian energy sector in the current difficult times. Another result is a strategy for the development of the Russian energy sector in order to attract additional investment. The novelty of the article includes the implied methodology of investment attractiveness and evidence of the high investment attractiveness of the Russian energy sector even in unstable conditions, especially in the COVID economic shock. Keywords: Energy sector, MNC, financial analysis, economic conjuncture, investment attractiveness, Russia JEL Classifications: P28, Q48 DOI: https://doi.org/10.32479/ijeep.10823